Analisis Praktik Kepemimpinan Servant Leadership Kepala sekolah SMP Kr. Gloria Pakuwon City - Zeffira Hianadi (Jurnal Ketopong Pendidikan, 2025)
Principal leadership plays a crucial role in shaping a school's work culture. However, there are not many studies describing how servant leadership practices are implemented by a Christian school principal. This study aims to provide a comprehensive description of servant leadership practices implemented by the principal of Kr. Gloria Pakuwon City Junior High School. The approach used in this study is a qualitative approach with a semi-structured face-to-face interview method and content analysis techniques to identify servant leadership characteristics that emerge in daily interactions. The results show that the principal consistently practices key characteristics of servant leadership such as humility, moral responsibility, empowerment and development of followers, wisdom in decision-making, and building a supportive and collaborative community. This study provides insight into how servant leadership can be implemented in the context of Christian schools and how principals can create a supportive and collaborative work climate and culture.